Integrated Advanced Medical Information Systems (IAIMS): Payoffs and Problems - Clayton, P. D. (Methods of Information in Medicine, 1994)
IAIMS (Integrated Advanced Information Management Systems) is an initiative to improve the access to information needed to provide patient care, health-oriented education, biomedical research, and management of large medical center environments. This paper will review the goals, history, and accomplishments of the IAIMS initiative. Shortcomings and frustrations, lessons learned, and the future of such initiatives will also be discussed.
Keywords: IAIMS; Workstations; Integration